(untitled) (Revista Brasileira Multidisciplinar, 2023)
Forage cactus (Opuntia and Nopalea) responds positively to cultural treatments such as weeding and weed cutting. However, the scarce labor and the high cost of labor is a challenge that producers, the scientific community and the government have to solve. The objective of this work was to evaluate 9 (nine) commercial herbicides and some mixtures of them in the control of weeds in the culture of forage cactus varieties Miúda (N. cochenillifera) and Orelha de Elefante Mexicana (O. stricta) in the municipality of Caruaru, Pernambuco, Brazil. Two experiments were carried out at the Experimental Station of the Agronomic Institute of Pernambuco (IPA) in Caruaru-PE. The designs used were in randomized blocks with three replications. The treatments evaluated were: 1. No weed control, 2. Hand weeding, 3. Mowing, 4. DMA®806BR (2,4-D), 5. GLYPHOSATE ATAR 48® (glyphosate)+DIURON NORTOX 500 SC ® (diuron), 6. GLYPHOSATE ATAR 48® (glyphosate)+AMERIS® (tebuthiurom), 7. HEXAZINONE-D NORTOX (hexazinone+diuron), 8. VOLCANE® (MSMA), 9. GOAL®BR (oxyfluorfen), 10. TARGA®50 BR (kizalofop-p-ethyl), 11. FUSILADE® 250 EW (fluasifop-p-butyl), 12. AMERIS® (tebutiuron), 13. GLYPHOSATE ATAR 48® (glyphosate)+DIURON NORTOX 500 SC ® (diuron)+AMERIS® (tebuthiuron). The botanical composition of the invasive plants, bare soil, survival, toxicity and productivity of fresh and dry matter of cactus were evaluated in the two years of cultivation. Among the identified species, those with the highest densities were: Ageratum conyzoides, Nicandra physalodes, Scoparia dulcis, Conyza bonariensis, Amaranthus viridis, Acanthospermum hispidum, Alternanthera tenella, Senegalia tenuifolia, Cordia goeldiana, Senegalia tenuifolia, Turnera subulata and Poaceae. The herbicides GLYPHOSATE ATAR 48®+AMERIS®; AMERIS®; and GLYPHOSATE ATAR 48®+DIURON NORTOX 500 SC®+AMERIS® were the most efficient in controlling weeds, due to high percentages of bare soil (75 to 99.67%), low toxicity (<8.33%) and high productivity of fresh (120.69 to 167.05 t.ha-1) and dry (21.75 to 24.40 t.ha-1) matter. Dry and fresh matter productivity was positively correlated with each other, and between bare soil and plant survival. Complementary studies are needed to support the Ministry of Agriculture, Livestock and Supply in the registration of products.